Comparison of acute physiological responses between one long and two short sessions of moderate-intensity training in endurance athletes - Kjøsen Talsnes, Rune; Torvik, Per-Øyvind; Skovereng, Knut; Sandbakk, Øyvind (Frontiers in Physiology, 2024)
Purpose To compare acute physiological responses and perceived training stress between one long and two short time- and intensity-matched sessions of moderate-intensity training in endurance athletes. Methods Fourteen male endurance athletes (VO2max: 69.2 ± 4.2 mL·min−1·kg−1) performed one 6 × 10-min interval session (SINGLE) and two 3 × 10-min interval sessions interspersed with 6.5 h recovery (DOUBLE) of moderate-intensity training on two separate days, while running in the laboratory, using a counterbalanced cross-over trial. The two training days were separated into a first part/session (interval stage 1–3) and second part/session (interval stage 4–6). Respiratory variables, heart rate (HR), blood lactate concentrations (BLa), and rating of perceived exertion (RPE) were collected during sessions, whereas supine heart rate (HR) was assessed in a 60-min recovery period following sessions. Measures of perceived training stress (1–10) were assessed in the morning of the subsequent day. Results HR, Bla, and RPE increased in the second compared to first part of SINGLE (168 ± 7 vs. 173 ± 7 bpm, 2.60 ± 0.75 vs. 3.01 ± 0.81 mmol·L−1, and 13.4 ± 1.0 vs. 14.8 ± 1.1-point, respectively, all p < 0.05). HR and Bla decreased in the second compared to first session of DOUBLE (171 ± 9 vs. 166 ± 9 bpm and 2.72 ± 0.96 vs. 2.14 ± 0.65 mmol·L−1, respectively, both p < 0.05). SINGLE revealed higher supine HR in the recovery period following sessions (65.4 ± 2.5 vs. 60.7 ± 2.5 bpm p < 0.05), session RPE (sRPE, 7.0 ± 1.0 vs. 6.0 ± 1.3-point, p = .001) and sRPE training load (929 ± 112 vs. 743 ± 98, p < 0.001) compared to DOUBLE. In the subsequent morning, increased levels of perceived fatigue and muscle soreness were observed following SINGLE compared to DOUBLE (7.0 ± 2.5 vs. 8.0 ± 1.0-point, p = .049 and 6.0 ± 2.5 vs. 7.0 ± 2.5-point, p = .002, respectively). Conclusion One long moderate-intensity training session was associated with a duration-dependent “drift” in physiological responses compared to two short time- and intensity-matched sessions, thereby suggesting a higher overall training stimulus. Simultaneously, the lower cost of the two shorter sessions indicates that such organization could allow more accumulated time at this intensity. Overall, these findings serve as a starting point to better understand the pros and cons of organizing moderate-intensity training as one long versus shorter sessions performed more frequently (e.g., as “double threshold training”) in endurance athletes.